PENGEMBANGAN LKPD BERBASIS PENEMUAN TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MATERI BANGUN RUANG SISI DATAR - Junaidi, Moh; Zabidi, Mohammad Naufal; Sholihah, Ummu; Asmarani, Dewi (Universitas Bhinneka PGRI, 2023)
The research objectives were to: (1) Know the validity (2) Know the practicality (3) Know the effectiveness, the results of the development of guided discovery-based student worksheets to improve critical thinking skills on flat sided space material for class VIII MTsN 1 Blitar. In this study using research and development methods (Research and Development / R D). The model used by the ADDIE model consists of five stages, namely Analysis, Design, Development, Implementation, Evaluation. Based on the product development steps, the ADDIE model is more rational and more complete than other development models, one of which is the 4D mode. The location of this research is at MTsN 1 Blitar. Data collection techniques in this study consisted of validation, questionnaires and tests. The data analysis technique used qualitative data analysis techniques and quantitative data analysis techniques.The results of this study consist of: (1) The results of the validity of the product validity of teaching materials in the research and development (RD) assessment of media experts are indicated by the validity levels of 82% and 70%. Meanwhile, from the assessment of material experts, the level of validity is 81% and 73%. Both media expert and material expert validation test showed that the product met the validity criteria. (2) The results of practicality seen from the student response questionnaire used, obtained an average value of 84.4% so that guided discovery-based worksheets can be said to be practical. (3) The effectiveness is seen from the students' post test questions, the results of the analysis conducted in the experimental class showed an average score of 88.53 while the control class had an average score of 77.41. This shows that students who use LKPD with guided discovery learning approach have higher learning outcomes and are able to improve critical thinking skills compared to students who do not use LKPD with guided discovery learning approach.